2020
DOI: 10.2147/copd.s233506
|View full text |Cite
|
Sign up to set email alerts
|

<p>Necroptosis Mediates Cigarette Smoke-Induced Inflammatory Responses in Macrophages</p>

Abstract: Introduction: Cigarette smoke (CS)-induced inflammation in macrophages is involved in the pathological process of chronic obstructive pulmonary disease (COPD). Necroptosis, which is a form of programmed necrosis, has a close relationship with robust inflammation, while its roles in COPD are unclear. Materials and Methods: Necroptosis markers were measured in mouse alveolar macrophages and cultured bone marrow-derived macrophages (BMDMs). Necroptosis inhibitors were used to block necroptosis in BMDMs, and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Mitochondrial oxidative stress plays a key role in CS-induced pulmonary disorders and is a predisposing factor in the pathogenesis of COPD [ 26 , 27 ]. Therefore, we next explored the role of CTTN in oxidative stress induced by CSC [ 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial oxidative stress plays a key role in CS-induced pulmonary disorders and is a predisposing factor in the pathogenesis of COPD [ 26 , 27 ]. Therefore, we next explored the role of CTTN in oxidative stress induced by CSC [ 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such oxidant challenge may increase LMP, which in turn may lead to impaired functions of LMs due to the cellular stress executed by increased LMP, and, if pronounced, the increase of LMP may even kill the LMs. 11,12,23,24 Unregulated death of LMs by necroptosis is associated with tobacco-smoke induced airway damage and COPD. 24 This scenario may be prevented by azithromycin, 25 a macrolide antibiotic used in the clinic to prevent COPD deterioration due to frequent exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,23,24 Unregulated death of LMs by necroptosis is associated with tobacco-smoke induced airway damage and COPD. 24 This scenario may be prevented by azithromycin, 25 a macrolide antibiotic used in the clinic to prevent COPD deterioration due to frequent exacerbations. In a series of studies of a variety of inflammatory and fibrotic lung diseases, we have previously presented observations suggesting that oxidant-induced LMP, mainly driven by a disturbed metabolism of iron and an accumulation of this metal inside lysosomes, 26 may be an important up-stream event in the cascade of events that trigger inflammation and/or fibrosis, 11,12,27,28 ultimately leading to CAL.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that necroptosis promotes inflammatory responses and mucin production at the cellular level [ 9 , 27 , 28 ]. In addition, the inhibition of necroptosis of macrophages exposed to CSE can also prevent the production of inflammatory cytokines [ 29 ]. Epithelial cells were co-cultured with macrophages under CSE exposure, pre-treated with necroptosis or apoptosis inhibitors and detected for inflammation-related markers.…”
Section: Necroptosis Induces Airflow Limitation In Copdmentioning
confidence: 99%
“…Mitochondrial ROS (mitoROS) modulates the occurrence of necroptosis in COPD, which leads to airflow limitation. Wang et al [ 29 ] specifically inhibited mitoROS in macrophages by mitochondria-targeted antioxidant (Mito-TEMPO) and confirmed that mitoROS mediates CSE-induced necroptosis and inflammatory responses, indicating that the necroptosis pathway is most likely dependent on mitoROS. Xu et al [ 9 ] treated PM-exposed human bronchial epithelial cells by Mito-TEMPO and found that PM exposure produces excessive mitoROS that activates the mitoROS-dependent early growth response gene-1 and therefore mediates the necroptosis of epithelial cells, whereas the mitoROS/early growth response gene-1/necroptosis pathway triggers two distinct signalling cascade responses (NF-κB and AP-1 pathways) to cause airway inflammation and mucus overproduction.…”
Section: Mechanism Of Necroptosis In Copdmentioning
confidence: 99%